1989
DOI: 10.1093/bja/63.6.692
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ketamine on Isolated Human Bronchial Preparations

Abstract: The bronchodilator effects of ketamine were examined in human bronchial preparations contracted maximally with histamine, acetylcholine, barium chloride or potassium chloride. Antagonism between ketamine and either histamine or acetylcholine was examined also. Ketamine caused bronchial relaxation irrespective of the constricting agent, and exerted a partial and non-competitive antagonism to histamine and acetylcholine. Propranolol and indomethacin did not inhibit the effect of ketamine, excluding the involveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 7 publications
0
11
0
1
Order By: Relevance
“…However, in the present study there was no functional or histological evidence of bronchodilation in normal rats anesthetized with ketamine. In this respect, Gateau et al (20) reported that ketamine did not influence the basal tone of human bronchial preparations but antagonized bronchial contraction produced by histamine and acetylcholine. The diversity of methods used to determine lung resistance, the variability in lung volume and respiratory frequency, the differences in lung preparations (in vivo versus in vitro), and the smooth muscle tone of the airways may lead to discrepant results.…”
Section: Discussionmentioning
confidence: 98%
“…However, in the present study there was no functional or histological evidence of bronchodilation in normal rats anesthetized with ketamine. In this respect, Gateau et al (20) reported that ketamine did not influence the basal tone of human bronchial preparations but antagonized bronchial contraction produced by histamine and acetylcholine. The diversity of methods used to determine lung resistance, the variability in lung volume and respiratory frequency, the differences in lung preparations (in vivo versus in vitro), and the smooth muscle tone of the airways may lead to discrepant results.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover the usefulness of ketamine, which produces significant cardiovascular stimulation and unpleasantness, including vivid dream-like experiences [18] has been also assessed in vitro [19,20]. In contrast, midazolam attenuated both the cardiostimulatory responses and unpleasant emergence reaction associated with ketamine [21].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated eosinophil counts are thus considered to be mirrored in the occult existence of allergic diseases. In general anesthesia, ketamine has been used safely against allergic reactions, especially for asthmatic patients because of its advantages for relaxing tracheal smooth muscle [34,35], and its ability to treat bronchospasm [11,12]. Since midazolam attenuated both the cardiostimulatory responses and unpleasant emergence associated with ketamine [36], the combination of midazolam and ketamine has been recommended for total intravenous anesthesia [13][14][15].…”
Section: Discussionmentioning
confidence: 99%